Assessing ecological knowledge, perceived agency, and motivations regarding wildlife and wildlife conservation in Samburu, Kenya. (October 2021) - Heisel, Sara E.; King, Elizabeth; Lekanta, Francis; Lemoile, Francis; Ryan, Camilla; Lemerketo, Isaya; Sundaresan, Siva; Malsbury, Erin; Bruyere, Brett
Abstract: In international wildlife conservation programs, community engagement and incentivization strategies (e.g., wildlife-related employment, tourism income) typically reflect the ecological understandings and motivations of Western conservationists who design them. However, these views may not always be shared by people who live alongside wildlife and are the intended beneficiaries of the incentives. Such misalignments can undermine the effectiveness of conservation efforts to motivate pro-conservation behavior. In Samburu, Kenya, an area with multiple active international conservation programs, we sought to assess local residents' perspectives regarding three factors known to influence pro-environmental behavior: (a) ecological knowledge, including views on wildlife abundance and extinction risk; (b) perceptions of agency regarding wildlife conservation (here defined as the ability of humans to influence wildlife populations); and (c) personal motivations for wildlife conservation. We interviewed 74 residents and evaluated whether their perspectives aligned with the premises and assumptions that underpin the strategies commonly used by international organizations to promote wildlife conservation in the area. We found that concepts of rarity and extinction based on Western-based science were not salient in how residents thought about local wildlife populations. Consistent with core assumptions of Western conservation programs, however, most residents did feel a sense of agency to influence wildlife populations, and reported economic incentives as primary motivations for conservation. We conclude with cautionary notes regarding tacit assumptions made when promoting wildlife conservation in other cultures, and the ethics and potential unintended consequences of 'motivation crowding' by powerful exogenous agents.